Chikusetsu Saponin V Attenuates MPP+-Induced Neurotoxicity in SH-SY5Y Cells via Regulation of Sirt1/Mn-SOD and GRP78/Caspase-12 Pathways - Ding Yuan (International Journal of Molecular Sciences, 2014)
Studies have shown that saponins from Panax japonicus (SPJ) possess neuroprotective effects. However, whether Chikusetsu saponin V (CsV), the most abundant member of SPJ, can exert neuroprotective effects against 1-methyl-4-phenylpyridinium ion (MPP+)-induced cytotoxicity is not known. In this study, we aimed to investigate the neuroprotective effects of CsV on MPP+-induced cytotoxicity in human neuroblastoma SH-SY5Y cells and explore its possible mechanisms. Our results show that CsV attenuates MPP+-induced cytotoxicity, inhibits ROS accumulation, and increases mitochondrial membrane potential dose-dependently. We also found that levels of Sirt1 protein and Mn-SOD mRNA significantly decreased in MPP+-treated group but were restored with CsV treatment in a dose-dependent manner. Furthermore, GRP78 protein and Caspase-12 mRNA levels were elevated by MPP+ exposure but reversed by CsV treatment. CsV inhibited the MPP+-induced downregulation of Bcl-2 and up-regulation of Bax in a dose-dependent manner and, thus, increased the ratio of Bcl-2/Bax. Overall, these results suggest that Sirt1/Mn-SOD and GRP78/Caspase-12 pathways might be involved in the CsV-mediated neuroprotective effects.